2011
DOI: 10.4061/2011/137459
|View full text |Cite
|
Sign up to set email alerts
|

Protein Methylation and Stress Granules: Posttranslational Remodeler or Innocent Bystander?

Abstract: Stress granules contain a large number of post-translationally modified proteins, and studies have shown that these modifications serve as recruitment tags for specific proteins and even control the assembly and disassembly of the granules themselves. Work originating from our laboratory has focused on the role protein methylation plays in stress granule composition and function. We have demonstrated that both asymmetrically and symmetrically dimethylated proteins are core constituents of stress granules, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2]. As many SGincorporated proteins are RNA-binding proteins and may be arginine-methylated [10], we analyzed whether SERBP1 interacts with these proteins. We first showed that hnRNPA1 co-immunoprecipitated with FLAGtagged SERBP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we observed the interaction of SERBP1 with asymmetric N G ,N G -dimethylarginine-containing proteins by co-immunoprecipitation [2]. As many SGincorporated proteins are RNA-binding proteins and may be arginine-methylated [10], we analyzed whether SERBP1 interacts with these proteins. We first showed that hnRNPA1 co-immunoprecipitated with FLAGtagged SERBP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein arginine methylation of some SG-incorporated RNA-binding proteins has been shown to be critical for their cellular distribution, and may further affect their sorting to SGs [10]. We are interested in whether arginine methylation of SERBP1 is related to its SG localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot discard the possibility that R-CRT, when present in SGs, regulate particular mRNA's encoding key antiapoptotic factors, thus either preventing its degradation necessary for the survival response or sequestering mRNA of proapoptotic proteins, inhibiting its translation. This is not the only case where a post-translational modification is involved in the assembly and remodeling of SGs (50). Other examples include the histone deacetylase 6 activity in SG formation (47), the inhibition of the ubiquitin proteasome system in SG disassembly (51), and the demonstration that SGs contain methylarginine proteins (52).…”
Section: Discussionmentioning
confidence: 99%
“…phosphorylation and glycosylation, of several SG components that are involved in the primary nucleation step play a significant role in the regulation of SG assembly/disassembly and function [20]. Moreover, several RNA-binding proteins, representing SG components, have been found to be asymmetrically and symmetrically dimethylated, suggesting that arginine modification is important in the process of SG formation as well [21]. The recruitment of FMRP to SGs is reduced under methylation inhibition [17].…”
Section: Introductionmentioning
confidence: 98%